Sagot :
x=46
Step-by-step explanation:
(√x+3)2 = (7)2
x+3 = 49
x -46 = 0
Add 46 to both sides
x = 46
A possible solution is :
x = 46
Original equation
√x+3 = 7
Plug in 46 for x
√(46)+3 = 7
Simplify
√49 = 7
Solution checks !!
Solution is:
x = 46
☁︎━━━━━━⍟━━━━━━☁︎
Given :-
[tex] \tt \sqrt{x + 3} = 7[/tex]
Steps :-
[tex] \looparrowright \sf\sqrt{x + 3} = 7[/tex]
[tex] \\ [/tex]
Squaring both side.
[tex] \looparrowright \sf(\sqrt{x + 3} ) {}^{2} = 7 {}^{2} [/tex]
[tex] \\ [/tex]
[tex] \looparrowright \sf{x + 3} = 7 {}^{2} [/tex]
[tex] \\ [/tex]
[tex] \looparrowright \sf{x + 3} = 49[/tex]
[tex] \\ [/tex]
[tex] \looparrowright \sf{x } = 49 - 3[/tex]
[tex] \\ [/tex]
[tex] \looparrowright \bold{x = 46}[/tex]
☁︎━━━━━━⍟━━━━━━☁︎
❥ τ᭄нє✞Blυє✞Sταr࿐